EDUCATION ON UNDERSTANDING OF INTELLECTUAL PROPERTY RIGHTS FOR JAJE UPAKARA MSME PRODUCTS IN SULAHAN VILLAGE - Dewi, Dewa Ayu Susanti; Adhiya Garini Putri, Dewa Ayu Putu (LPPM Univ. Ibn Khaldun Bogor, 2023)
The existence of MSMEs (Micro, Small, and Medium Enterprises) as community businesses in Sulahan Village is quite lot of existence, but knowledge about IPR (Intellectual Property Rights) is still minimal. One of the problems found in Sulahan Village is the knowledge of the MSME owner community regarding the procedures for registering IPR. An alternative that can protect MSMEs from IPR protection is to register MSMEs with the Ministry of Law and Human Rights. By registering the trademark of the MSME, the MSME gets legal protection. IPR registration can be beneficial for MSME actors. This is useful for the protection of a brand, copyrighted work, and product for these MSME business actors. Thus, MSME actors can avoid similarity or plagiarism of other brands, and avoid lawsuits. Through the IPR Education program for MSMEs, it is expected to increase insight and knowledge for MSME owners about the importance of IPR for legal protection. Based on these problems, the author through Community Service activities has carried out IPR Counseling for Jaje Upakara MSMEs in Sulahan Village. The method used is to provide education on understanding IPR, which is carried out through three stages. Namely: the stage of observation, interview, and implementation of work programs in Sulahan Village. The results of the education carried out are in the form of knowledge about IPR Registration to the public and products in the form of PPT.